A rare case of Solitary Fibrous Tumor of Subglottis - Sumana CV; Suhel Hasan; Betty Mariam Jacob; Rajeswarie RT (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Solitary Fibrous Tumor is a rare benign mesenchymal tumor, described as a primary pleural lesion. 50% of the cases are seen in the thorax and only 6 % develop in the head and neck region. Laryngeal involvement  is rare, mostly involving the supraglottic larynx. We report a case of Solitary fibrous tumor of the subglottic larynx, which displayed positivity to Immunohistochemical marker CD34, and was excised surgically by an external approach.